Binder‐Free Electrodes Derived from Interlayer‐Expanded MoS2 Nanosheets on Carbon Cloth with a 3D Porous Structure for Lithium Storage. Issue 8 (29th April 2019) - Han, Yan; Chatti, Manjunath; Ge, Yu; Wang, Caiyun; Chao, Yunfeng; Simonov, Alexandr N.; Wallace, Gordon G.
Abstract: Anchoring nanostructured MoS2 on a conductive carbon substrate is an effective approach to produce flexible binder‐free electrodes for energy storage applications. However, they are commonly fabricated through time‐consuming hydrothermal reactions. Herein, MoS2 nanosheet arrays grown on a flexible carbon fiber cloth (CC) have been synthesized within 2 h by using a microwave‐assisted method. These vertically aligned MoS2 nanosheets with expanded interlayer spacing of approximately 1 nm densely cover the support surface and form an interconnected network with significant void space. When employed as anodes for lithium‐ion batteries, the microwave‐synthesized binder‐free MoS2 /CC composites exhibit a high areal capacity of 2.5 mAh cm −2 at 0.15 mA cm −2, excellent cycle performance, and good rate capability. Abstract : Top performer : MoS2 nanosheets with expanded interlayer spacing are fabricated on carbon cloth (CC) by using a simple microwave‐assisted solvothermal method. This 3D hierarchical MoS2 /CC composite, as a free‐standing electrode, demonstrates excellent lithium storage performance.